2012
DOI: 10.1021/om3001185
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrochemical Anion-Sensing Properties of a Biferrocenyl-Functionalized Dendrimer

Abstract: The synthesis and electrochemical anionsensing properties of a diaminobutane poly(propyleneimine) dendrimer functionalized with biferrocenyl units 2 are presented. The redox activity of the ferrocenyl centers in 2 has been characterized by cyclic voltammetry. Cyclic and square wave voltammetric investigations demonstrate that tetraferrocenyl compound 2 and the reference compound 1 show electrochemical anion-sensing action: they display a cathodic shift of the ferrocene−ferrocenium redox couple with dihydrogenp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…31 In contrast to the variety of synthetic routes to tetraferrocenyl compounds, few have been reported for dimerizations using diferrocenyl building blocks. [13][14][15] Notably, Mueller-Westerhoff used the coordination of a diferrocenyl dithiolate to a Ni center to afford a tetraferrocenyl complex. 14a In the present study, we used the coordination of a diferrocenyl catecholate to a boron center to afford K4, whose structural feature is a tetracoordinated boron anionic bridge.…”
Section: Synthesis and Characterization Of Di-and Tetra-ferrocenyl Sp...mentioning
confidence: 99%
See 2 more Smart Citations
“…31 In contrast to the variety of synthetic routes to tetraferrocenyl compounds, few have been reported for dimerizations using diferrocenyl building blocks. [13][14][15] Notably, Mueller-Westerhoff used the coordination of a diferrocenyl dithiolate to a Ni center to afford a tetraferrocenyl complex. 14a In the present study, we used the coordination of a diferrocenyl catecholate to a boron center to afford K4, whose structural feature is a tetracoordinated boron anionic bridge.…”
Section: Synthesis and Characterization Of Di-and Tetra-ferrocenyl Sp...mentioning
confidence: 99%
“…Heinze et al reported dimers of mixed-valence biferrocene amino acids linked by ureylene and amide bridges, and the effects of the bridges on the potential splitting. 15 In their pioneering work, they showed that the amide bridge affects the potential splitting of the resulting tetraferrocenyl dimer (1e − /1e − /2e − process), but the ureylene bridge has not largely effected (2e − / 2e − process). A comparison of 3 and K4 in the present study revealed that linking the diferrocenyl units (FcCFc) with the spiroborate motif increased the potential spread.…”
Section: Electrochemical Behaviors Of 3 and K4 In Dmfmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, receptors containing the ferrocene moiety are especially valuable as electrochemical anion sensors, since this chemically robust metallocene undergoes fast and reversible one-electron oxidation to the positively charged ferrocenium form at accessible potentials. Surprisingly, and although a wide number of ferrocene-based redox-active receptors bearing N–H groups such as amide, urea, thiourea, triazole, amidine, guanidine, and aminosilane moieties have been reported, the use of ferrocene-containing receptors incorporating the Si–OH group as an anion recognition motif remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, redox-active ferrocene-containing highly branched polymers are good candidates to play a key role as multielectron transfer mediators in electrochemical response processes of biological and industrial importance [20,21]. Literature survey revealed that the redox-responsive ferrocene unit has been incorporated into amide [22], urea [23], thiourea [24], dendrimers [25] and imidazole [26] moieties to construct the anion receptors with electrochemical sensing properties.…”
Section: Introductionmentioning
confidence: 99%